Identification of Novel TRPC5 Inhibitors by Pharmacophore-Based and Structure-Based Approaches. (August 2020) - Li, Shuxiang; Zhang, Shuqun; Chen, Dingyuan; Jiang, Xuan; Liu, Bin; Zhang, Hongbin; Rachakunta, Munikishore; Zuo, Zhili
Graphical Abstract: Highlights: Ligand-based virtual screening (LBVS) and structure-based virtual screening (SBVS) methods was used to identify potential TRPC5 inhibitors. LBVS was based on a combination of HipHop pharmacophore and HypoGen pharmacophore. SBVS was based on generating homology model and subsequent molecular docking studies. Seven compounds were selected using Lipinski's Rule of Five, Veber rules, ADME properties and PAINS filter. Abstract: Canonical transient receptor potential-5 (TRPC5), which belongs to the subfamily of transient receptor potential (TRP) channels, is a non-selective cation channel mainly expressed in the central nervous system and shows more restricted expression in the periphery. TRPC5 plays a crucial role in human physiology and pathology, for instance, anxiety, depression, epilepsy, pain, memory and chronic kidney disease (CKD). However, due to lack of the effective and selective inhibitors, its physiological and pathological mechanism remains so far unknown. It is therefore pivotal to identify potential TRPC5 inhibitors. We have applied ligand-based virtual screening (LBVS) and structure-based virtual screening (SBVS) methods. The pharmacophore models of TRPC5 antagonists generated by using the HypoGen and HipHop algorithms were used as a query model for the screening of potential inhibitors against the Specs database. The resultant hits from LBVS were further screened by SBVS. SBVS was carried out based on the homology model generation of human TRPC5, binding site identification, molecular dynamics optimization and molecular docking studies. In our systematic screening approaches, we have identified 7 hits compounds with comparable dock score after Lipinski and Veber rules, ADMET, PAINS analysis, cluster analysis, and similarity analysis. In conclusion, the current research provides novel backbones for the new-generation of TRPC5 inhibitors.